Optimalisasi Pemahaman Matematika Santri MTs Swasta Darularafah dengan Sistem Pendukung Keputusan Berbasis VIKOR - Khairunnisa Ani Putri; Sofiah Aini; Rika Hanifah Tanjung; Nursakila Ena Anjani (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
Modern Islamic boarding schools not only focus on religious education, but are also required to improve the academic quality of students, including in mathematics subjects which are often challenging due to differences in students' learning styles, motivations, and abilities. This study aims to design and implement a Decision Support Sistem (DSS) based on the VIKOR method to analyze students' mathematical understanding and provide recommendations for more adaptive learning strategies. The study uses a descriptive quantitative approach with data obtained through documentation of students' grades, as well as interviews with mathematics teachers. The VIKOR method is used to evaluate students' understanding based on five main criteria, namely exam scores, report card scores, attendance, attitudes and behavior, and skills, through a process of normalization, weighting, calculation of S, R, and Q scores, and ranking students. The results show that there are five students with the lowest level of mathematical understanding, namely A11, A4, A17, A1, and A12, who have the lowest VIKOR index scores. This low level of understanding is influenced by factors such as learning attitudes, attendance, report card scores, and skills, so they require further attention and guidance from teachers. The application of the VIKOR method in SPK has proven effective in optimizing the analysis of students' mathematics achievements and providing recommendations for more targeted personal learning strategies, thereby helping to improve the quality of education and maximize students' academic potential.